ANALISA PEMELIHARAAN PATIENT MONITOR di UPTD PUSKESMAS TELUK DALAM - Ratahati Gaurifa; Siti Rahmah (JURNAL MUTIARA ELEKTROMEDIK, 2020)
"Analysis of Patient Monitor Maintenance at the UPTD public healty center Teluk dalam".Continuous health services need to be supported by equipment that is always ready to use and can function properly. This requires public healty center management to be able to manage and maintain medical equipment effectively and efficiently. This study aims to determine the implementation of patient monitor maintenance at the UPTD public healty center Teluk dalam. This research is a descriptive study with a quantitative survey method. The instrument used is to collect data. The results of this study indicate the aspects of natural resource input, processes, and outputs. The results of this study indicate that in practice, it cannot run properly, caused by limited technicians, lack of training, and maintenance SOP are not in accordance with procedures. It is recommended that the public healty center management pay more attention to the equipment maintenance system (input, process, and output) in order to avoid the problem of equipment damage and to work optimally.